Examining the Effects of Organizational Culture and Transformational Leadership on Teacher Performance: The Mediating Role of Job Satisfaction - Yoserizal Yoserizal; Sutiyem Sutiyem; Desy Trimiyanti; Yulina Eliza (International Journal of Entrepreneurship and Business Management, 2026)
This study aims to analyze the role of organizational and leadership factors in enhancing teacher performance at SMP Negeri 1 Padang Laweh. The variables examined include organizational culture, transformational leadership, and job satisfaction as independent variables, while teacher performance serves as the dependent variable. The study employed a quantitative approach using a survey method. The population of this research consisted of all teachers at SMP Negeri 1 Padang Laweh, with a total sample of 33 respondents determined through a saturated sampling (census) technique. Data were collected through questionnaire distribution, while the data analysis technique applied was multiple linear regression analysis using SPSS software. The partial test results revealed that organizational culture has a significant effect on teacher performance with a significance value of 0.006. Transformational leadership also demonstrated a significant influence with a significance value of 0.000, while job satisfaction showed a significant effect with a significance value of 0.013. Furthermore, the Sobel test produced a Z-value of 3.96, which exceeded the critical value of 1.96, indicating that job satisfaction significantly mediates the relationship between organizational culture, transformational leadership, and teacher performance. These findings suggest that a positive organizational culture, effective transformational leadership, and high levels of job satisfaction contribute substantially to enhancing teacher performance.